SrNb2O6-x nanofiber material as well as preparation method and application thereof
By using the periodic Lewis acid-base pair and oxygen vacancy structure of SrNb2O6-x nanofiber materials in the photocatalyst, the problem of insufficient CO2 adsorption and activation in existing photocatalysts is solved, and the adsorption and photocatalytic activity of CO2 is significantly improved, and the Efficient CO2 reduction reaction.
Patent Information
- Application Number
- CN202411307256.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2024-12-27
AI Technical Summary
The Lewis acid and base pairs are randomly distributed in existing photocatalysts, resulting in less obvious CO2 adsorption and activation, and it is difficult to efficiently adsorb CO2, affecting the CO2 conversion efficiency.
SrNb2O6-x nanofiber material is used, and its Lewis acid-base pairs are arranged periodically, including Sr2+ and Nb4+. The oxygen vacancy is formed by treating reducing organic matter solutions to improve the CO2 adsorption capacity.
It significantly improves the adsorption and activation ability and photocatalytic activity of CO2, enhances the adsorption and light absorption properties of CO2, and improves the efficiency of CO2 reduction reaction.
Smart Images

Figure CN119194848A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of catalytic technology, in particular to a SrNb2O 6-x Nanofiber material and its preparation method and application. Background Art
[0002] The rapid development of global industry has led to a sharp increase in the CO2 content in the atmosphere, seriously disrupting the carbon cycle balance in nature. The related energy and environmental problems are becoming increasingly serious and have attracted close attention worldwide.
[0003] Photocatalytic technology can simulate natural photosynthesis and use solar energy to convert excess CO2 into high-value-added chemicals, helping to reduce dependence on traditional fossil energy. Since the linear structure of CO2 molecules is thermodynamically stable (the dissociation energy of C=O is as high as 750kJ·mol -1 ), making the activation of CO2 molecules a very challenging research topic. Therefore, developing and designing photocatalysts that can efficiently adsorb CO2 to achieve sustainable and rapid conversion of CO2 molecules is an effective way to solve the energy crisis and environmental pollution.
[0004] As we all know, the first step of photocatalytic CO2 reduction is the adsorption of CO2 on the surface of the photocatalyst, so the adsorption behavior is considered to be one of the important factors affecting the CO2 conversion efficiency. Studies have shown that Lewis acid-base pairs are helpful for the adsorption and activation of CO2 molecules. Common Lewis acid-base pairs used for CO2 reduction photocatalysts include In(OH) 3–x (ACS Catal.2023,13,6214-6221), ZnIn2S4–AlOOH (Catalysis Science&Technology 2024,14(10),2868-2875.), In@InO x H y (Dalton Transactions 2023, 52(35), 12543), in these photocatalysts, the Lewis acid-base pairs are randomly distributed in space and are generally composed of hydroxide and metal ions. Although these photocatalysts have a certain adsorption and activation effect on CO2 molecules, the adsorption and activation effect is not obvious. Summary of the invention
[0005] The object of the present invention is to provide a SrNb2O 6-x Nanofiber material and preparation method and application thereof. The SrNb2O 6-x Nanofiber materials, as acid-base photocatalysts, have high adsorption capacity for CO2 and exhibit high catalytic activity in the photocatalytic CO2 reduction reaction.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a SrNb2O 6-x The nanofiber material comprises SrNb2O6 nanofibers, and Lewis acid-base pairs and oxygen vacancies distributed on the surface of the SrNb2O6 nanofibers; in the Lewis acid-base pairs, the Lewis acid is Sr 2+ , the Lewis base is Nb 4+ The Lewis acid and Lewis base are arranged periodically respectively; the SrNb2O6 nanofibers are composed of SrNb2O6 crystals.
[0008] Preferably, the SrNb2O6 crystal is monoclinic.
[0009] The present invention provides the SrNb2O 6-x The method for preparing the nanofiber material comprises the following steps:
[0010] The SrNb2O6 nanofibers are immersed in a reducing organic solution and then taken out to obtain SrNb2O6 nanofibers with the reducing organic solution attached to the surface; the SrNb2O6 nanofibers are composed of SrNb2O6 crystals;
[0011] The SrNb2O6 nanofibers with the reducing organic solution attached to their surfaces are annealed under vacuum conditions. 5+ Reduced to Nb 4+ At the same time, oxygen vacancies are formed to obtain the SrNb2O 6-x Nanofiber materials.
[0012] Preferably, the reducing organic matter in the reducing organic matter solution includes alcohol and / or aldehyde; and the concentration of the reducing organic matter solution is 0.05-0.5%.
[0013] Preferably, the annealing temperature is 200-400° C., and the holding time is 1-2 hours.
[0014] Preferably, the method for preparing the SrNb2O6 nanofibers comprises the following steps:
[0015] dissolving a divalent strontium salt, a pentavalent niobium salt and an organic template agent in a solvent to obtain a spinning solution;
[0016] Electrospinning the spinning solution to obtain metal salt-template composite nanofibers;
[0017] The metal salt-template composite nanofibers are calcined in an air atmosphere to obtain the SrNb2O6 nanofibers.
[0018] Preferably, the calcination temperature is 500-850° C., and the holding time is 1-6 hours.
[0019] Preferably, the organic template includes one or more of polyvinyl pyrrolidone, polyacrylonitrile and polyvinyl alcohol.
[0020] Preferably, the molar ratio of Sr in the divalent strontium salt to Nb in the pentavalent niobium salt is 1:2; the mass ratio of the total mass of the divalent strontium salt and the pentavalent niobium salt to the mass of the organic template is (0.2-0.6):1.
[0021] The present invention provides the SrNb2O 6-x Nanofiber material or SrNb2O prepared by the preparation method described in the above scheme 6-x Application of nanofiber materials as photocatalysts in photocatalytic reduction of CO2.
[0022] The present invention provides a SrNb2O 6-x The nanofiber material comprises SrNb2O6 nanofibers, and Lewis acid-base pairs and oxygen vacancies distributed on the surface of the SrNb2O6 nanofibers; in the Lewis acid-base pairs, the Lewis acid is Sr 2+ , the Lewis base is Nb 4+ The Lewis acid and Lewis base are arranged periodically; the SrNb2O6 nanofibers are composed of SrNb2O6 crystals. 6-x Nanofiber materials are different from existing acid-base photocatalysts. Specifically, in the present invention, Lewis acid-base pairs are periodically arranged on the fiber surface, which greatly increases the number of acidic sites and basic sites, can adsorb a large amount of CO2, and improve the CO2 activation ability. Moreover, the nanofiber material of the present invention is composed of SrNb2O6 crystals. The lattice stress can prevent the basic sites in the Lewis acid-base pairs from combining with the acidic sites, causing a sharp decrease in the number of active sites. The Lewis acid-base pairs of existing photocatalysts are randomly distributed. Once the number increases, it is easy for the acidic sites to combine with the basic sites. Therefore, the number of Lewis acid-base pairs in existing photocatalysts is relatively small. On the other hand, the Lewis acid-base pairs of the present invention are bimetallic acid-base pairs, that is, the Lewis acid and the Lewis base are both metal ions. More specifically, the Lewis acid is Sr 2+ , the Lewis base is Nb 4+ , which has a significant adsorption and activation effect on CO2 molecules; in addition, the presence of oxygen vacancies is also conducive to the adsorption of CO2 molecules and the absorption of light. 6-x Nanofiber materials exhibit excellent light absorption and high adsorption of CO2, which greatly improves their activity in the photocatalytic CO2 reduction reaction. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 SrNb2O prepared in Example 3 6-x -3 Scanning electron microscope images of nanofibers;
[0024] Figure 2 SrNb2O prepared in Examples 1 to 3 6-x X-ray diffraction patterns of the nanofiber material and the SrNb2O6 nanofiber prepared in Comparative Example 1;
[0025] Figure 3 SrNb2O prepared in Example 3 6-x -3 Spherical aberration corrected electron micrograph of nanofibers;
[0026] Figure 4 SrNb2O prepared in Example 3 6-x -3 electron paramagnetic resonance spectra of SrNb2O6 nanofibers prepared in nanofiber and comparative example 1;
[0027] Figure 5 SrNb2O prepared in Example 3 6-x -3 nanofibers and the UV-visible absorption spectra of the SrNb2O6 nanofibers prepared in Comparative Example 1;
[0028] Figure 6 SrNb2O prepared in Example 3 6-x -3 CO2 isotherm adsorption curves of SrNb2O6 nanofibers prepared in nanofibers and comparative example 1;
[0029] Figure 7 SrNb2O prepared in Examples 1 to 3 6-x Comparative curve of CO2 performance of nanofiber material and SrNb2O6 nanofiber prepared in comparative example 1. DETAILED DESCRIPTION
[0030] The present invention provides a SrNb2O 6-x The nanofiber material comprises SrNb2O6 nanofibers, and Lewis acid-base pairs and oxygen vacancies distributed on the surface of the SrNb2O6 nanofibers; in the Lewis acid-base pairs, the Lewis acid is Sr 2+ , the Lewis base is Nb 4+ The Lewis acid and Lewis base are arranged periodically respectively; the SrNb2O6 nanofibers are composed of SrNb2O6 crystals.
[0031] The present invention is to SrNb2O 6-xThere is no special requirement for the value of x, which is related to the amount of oxygen vacancies on the surface of the nanofiber material. In the present invention, the presence of oxygen vacancies is beneficial to the adsorption of CO2 molecules and the absorption of light.
[0032] In the present invention, the SrNb2O 6-x The diameter of the nanofiber material is preferably 10 to 60 nm.
[0033] In the present invention, the SrNb2O6 crystal is preferably a monoclinic crystal.
[0034] Compared with the random distribution of Lewis acid-base pairs in existing photocatalysts, once the number increases, it is easy for acidic sites to combine with basic sites, resulting in a small number of Lewis acid-base pairs in existing photocatalysts. In the present invention, Lewis acid-base pairs are arranged periodically on the fiber surface, which greatly increases the number of Lewis acidic sites and Lewis basic sites, can adsorb a large amount of CO2, and improve the CO2 activation ability. Moreover, the nanofiber material of the present invention is composed of SrNb2O6 crystals, and the lattice stress can prevent the basic sites in the Lewis acid-base pairs from combining with the acidic sites, resulting in a sharp decrease in the number of active sites. In addition, the Lewis acid-base pair of the present invention is a bimetallic acid-base pair, specifically, the Lewis acid is Sr 2+ , the Lewis base is Nb 4 + , and its adsorption and activation effect on CO2 molecules is obvious.
[0035] The present invention provides the SrNb2O 6-x The method for preparing the nanofiber material comprises the following steps:
[0036] The SrNb2O6 nanofibers are immersed in a reducing organic solution and then taken out to obtain SrNb2O6 nanofibers with the reducing organic solution attached to the surface; the SrNb2O6 nanofibers are composed of SrNb2O6 crystals;
[0037] The SrNb2O6 nanofibers with the reducing organic solution attached to their surfaces are annealed under vacuum conditions. 5+ Reduced to Nb 4+ At the same time, oxygen vacancies are formed to obtain the SrNb2O 6-x Nanofiber materials.
[0038] In the present invention, unless otherwise specified, the raw materials and equipment used are commercially available products well known in the art.
[0039] The SrNb2O6 nanofibers are first described below.
[0040] In the present invention, the SrNb2O6 nanofiber is preferably obtained by self-production; the preparation method of the SrNb2O6 nanofiber preferably comprises the following steps:
[0041] dissolving a divalent strontium salt, a pentavalent niobium salt and an organic template agent in a solvent to obtain a spinning solution;
[0042] Electrospinning the spinning solution to obtain metal salt-template composite nanofibers;
[0043] The metal salt-template composite nanofibers are calcined in an air atmosphere to obtain the SrNb2O6 nanofibers.
[0044] In the present invention, the divalent strontium salt, the pentavalent niobium salt and the organic template are preferably dissolved in a solvent to obtain a spinning solution.
[0045] In the present invention, the divalent strontium salt preferably includes one or more of strontium carbonate, strontium chloride and strontium acetate, more preferably strontium acetate; the pentavalent niobium salt preferably includes one or more of niobium ethoxide, niobium oxalate and niobium pentachloride, more preferably niobium oxalate; the molar ratio of Sr in the divalent strontium salt to Nb in the pentavalent niobium salt is preferably 1:2.
[0046] In the present invention, the organic template preferably includes one or more of polyvinyl pyrrolidone, polyacrylonitrile and polyvinyl alcohol, and more preferably polyvinyl pyrrolidone. In the present invention, the relative molecular weight of the polyvinyl pyrrolidone is preferably above 900,000; the relative molecular weight of the polyacrylonitrile is preferably above 150,000; the relative molecular weight of the polyvinyl alcohol is preferably above 80,000. The present invention does not impose any special restrictions on the upper limit of the relative molecular weight of the organic template. Under the premise that electrospinning can be carried out, the higher the relative molecular weight of the organic template and the longer its chain length, the better the template effect of the formed nanofibers, and the better the SrNb2O6 nanofiber structure is maintained after the template is removed by calcination. In an embodiment of the present invention, the organic template is polyvinyl pyrrolidone with a relative molecular weight of 1.3 million.
[0047] In the present invention, the mass ratio of the total mass of the divalent strontium salt and the pentavalent niobium salt to the organic template is preferably (0.2-0.6):1, more preferably (0.3-0.5):1, and further preferably (0.35-0.4):1.
[0048] In the present invention, the solvent preferably includes one or more of N,N-dimethylformamide, ethanol, chloroform and water, and more preferably N,N-dimethylformamide. When the solvent includes multiple of the above substances, the present invention has no special requirements for the ratio of each solvent, and any ratio is acceptable. The present invention preferably selects a suitable solvent according to the type of organic template, and the solvent can completely dissolve the divalent strontium salt, the pentavalent niobium salt and the organic template. In an embodiment of the present invention, the organic template is polyvinyl pyrrolidone, and the solvent is selected from N,N-dimethylformamide.
[0049] In the present invention, the usage ratio of the organic template and the solvent is preferably (0.8-1.5) g:10 mL, and more preferably (1.0-1.3) g:10 mL.
[0050] The present invention has no special requirements for the dissolution process, as long as the divalent strontium salt, pentavalent niobium salt and organic template are completely dissolved. In an embodiment of the present invention, the divalent strontium salt and pentavalent niobium salt are first added to the solvent and stirred until completely dissolved, and then the organic template is added and stirred to fully dissolve.
[0051] After obtaining the spinning solution, the present invention preferably performs electrostatic spinning on the spinning solution to obtain metal salt-template composite nanofibers.
[0052] The present invention has no special requirements for the specific implementation of the electrospinning, and the electrospinning method known in the art can be used. In the embodiment of the present invention, the spinning solution is loaded into a medical syringe with a nozzle, the distance between the nozzle and the grounded receiving plate is adjusted, and a platinum electrode is placed in the spinning solution to apply high voltage for spinning to perform electrospinning.
[0053] In the present invention, the conditions for electrospinning preferably include: a spinning voltage of 8 to 15 kV, a receiving distance of 10 to 16 cm, and a nozzle diameter of 0.3 to 0.8 mm; further, the spinning voltage is more preferably 9 to 12 kV, the receiving distance is more preferably 12 to 15 cm, and the nozzle diameter is more preferably 0.4 to 0.6 mm.
[0054] After obtaining the metal salt-template composite nanofibers, the present invention preferably calcines the metal salt-template composite nanofibers in an air atmosphere to obtain the SrNb2O6 nanofibers.
[0055] In the present invention, the calcination temperature is preferably 500-850°C, more preferably 600-800°C; the calcination holding time is preferably 1-6h, more preferably 2h. In the present invention, the rate of heating to the calcination temperature is preferably 1-10°C / min, more preferably 2-5°C / min. The present invention removes the organic template by calcination.
[0056] In the present invention, the SrNb2O6 nanofibers prepared by the above method are composed of SrNb2O6 crystals, specifically belonging to the monoclinic system. The SrNb2O6 nanofibers have a double acid site structure. 2+ and Nb 5+ All are Lewis acids.
[0057] After obtaining the SrNb2O6 nanofibers, the present invention immerses the SrNb2O6 nanofibers into a reducing organic solution, takes them out, and obtains the SrNb2O6 nanofibers with the reducing organic solution attached to the surface.
[0058] In the present invention, the reducing organic solution is preferably an aqueous solution of reducing organics; the reducing organics preferably include alcohols and / or aldehydes, the alcohols preferably include methanol and / or ethanol; the aldehydes preferably include formaldehyde and / or acetaldehyde; the concentration of the reducing organic solution is preferably 0.05-0.5%, more preferably 0.05-0.2%, and most preferably 0.15%. The present invention controls the number of Lewis acid-base pairs by controlling the concentration of the reducing organic solution. Within the above range, the higher the concentration, the greater the number of Lewis acid-base pairs.
[0059] The present invention has no special requirements for the amount of the reducing organic solution, as long as it can completely immerse the SrNb2O6 nanofibers. In the present invention, the immersion is preferably carried out at room temperature, that is, no additional heating or cooling is required; the immersion time is preferably 0.5 to 2 hours, more preferably 1 to 1.5 hours. The present invention causes the surface of the SrNb2O6 nanofibers to carry reducing organic matter through immersion.
[0060] After obtaining the SrNb2O6 nanofiber with the reducing organic solution attached to the surface, the present invention anneals the SrNb2O6 nanofiber with the reducing organic solution attached to the surface under vacuum conditions, and the Nb 5+ Reduced to Nb 4+ At the same time, oxygen vacancies are formed to obtain the SrNb2O 6-x Nanofiber materials.
[0061] In the present invention, the annealing temperature is preferably 200-400°C, more preferably 250-350°C, and further preferably 300°C; the annealing holding time is preferably 1-2h; the rate of heating to the annealing temperature is preferably 0.5-6°C / min, more preferably 2-4°C / min. In the present invention, the vacuum degree of the vacuum condition is preferably -0.05MPa to -0.1MPa. In the present invention, the annealing is preferably performed in a tube furnace.
[0062] In the annealing process of the present invention, under the action of reducing organic matter, Nb 5+ Reduced to Nb 4+ , Sr. 2+ The valence state remains unchanged, and at the same time, O on the surface of SrNb2O6 nanofibers is taken away to form oxygen vacancies.
[0063] In the present invention, since the SrNb2O6 nanofibers are crystalline structures, each particle is repeated periodically. Therefore, after annealing, the Lewis acid (Sr 2+ ) and Lewis base (Nb 4+ ) are all arranged periodically.
[0064] The present invention provides the SrNb2O 6-x Nanofiber material or SrNb2O prepared by the preparation method described in the above scheme 6-x Application of nanofiber materials as photocatalysts in photocatalytic reduction of CO2.
[0065] In the present invention, the light excitation wavelength of the photocatalytic reduction of CO2 reaction is preferably 320nm to 2500nm; in the embodiment of the present invention, a 300W xenon lamp is used as the light source, and the light density is 150mW / cm 2 .
[0066] The present invention has no special requirements for the specific implementation process of the photocatalytic reduction of CO2 reaction, and the implementation process known in the art can be used. In the embodiment of the present invention, SrNb2O 6-x The nanofiber material is dispersed in water as a photocatalyst, then coated on a glass sheet and dried. The glass sheet with the photocatalyst attached is placed in a closed reactor, CO2 gas is introduced into the closed reactor, and a reduction reaction is carried out under light conditions.
[0067] Different from the existing acid-base photocatalysts, in the present invention, the Lewis acid-base pairs are arranged periodically on the fiber surface, which greatly increases the number of Lewis acid sites and Lewis basic sites compared with the random arrangement, and can adsorb a large amount of CO2 and improve the CO2 activation ability. Moreover, the nanofiber material of the present invention is composed of SrNb2O6 crystals, and the lattice stress can prevent the basic sites in the Lewis acid-base pairs from combining with the acid sites, resulting in a sharp decrease in the number of active sites. On the other hand, the Lewis acid-base pairs of the present invention are bimetallic acid-base pairs, that is, the Lewis acid and the Lewis base are both metal ions, and more specifically, the Lewis acid is Sr 2+ , the Lewis base is Nb 4+ , which has a significant adsorption and activation effect on CO2 molecules. 6-xNanofiber materials were used as photocatalysts for CO2 reduction and showed high catalytic activity.
[0068] The SrNb2O 6-x The nanofiber material and its preparation method and application are described in detail, but they should not be understood as limiting the scope of protection of the present invention.
[0069] Comparative Example 1
[0070] Dissolve 0.3225g of niobium oxalate and 0.06165g of strontium acetate in 10mL of N,N-dimethylformamide, stir thoroughly to dissolve, then dissolve 1.0g of high molecular weight polyvinyl pyrrolidone with a relative molecular weight of 1.3 million in the above solution, stir thoroughly to dissolve as a spinning solution. Next, the spinning solution is loaded into a medical syringe with a nozzle of 0.4mm in diameter, the distance between the nozzle and the grounded receiving plate is kept at 15cm, and a platinum electrode is placed in the solution and a high voltage of 10kV is applied to perform electrostatic spinning to prepare metal salt-template composite nanofibers. Finally, the temperature is raised to 800℃ in a muffle furnace at a rate of 2℃ / min, and the temperature is kept for 2h to calcine the metal salt-template composite nanofibers to obtain SrNb2O6 nanofibers.
[0071] Example 1
[0072] 10 mg of the SrNb2O6 nanofibers prepared in the comparative example 1 were weighed and immersed in 10 mL of 0.05% ethanol aqueous solution for 1 h. The fibers were taken out and transferred to a tube furnace. The vacuum degree in the tube was set to -0.1 MPa, and then the temperature was raised to 300 ° C at a rate of 2 ° C / min and kept for 1 h to obtain SrNb2O6 nanofibers with surface periodic acid-base pairs. 6-x Nanofiber material, denoted as SrNb2O 6-x -1 nanofiber.
[0073] Example 2
[0074] 10 mg of the SrNb2O6 nanofibers prepared in Comparative Example 1 were weighed and immersed in 10 mL of 0.10% ethanol aqueous solution for 1 h. The fibers were taken out and transferred to a tube furnace. The vacuum degree in the tube was set to -0.1 MPa, and then the temperature was raised to 300 ° C at a rate of 2 ° C / min and kept for 1 h to obtain SrNb2O6 nanofibers with surface periodic acid-base pairs. 6-x Nanofiber material, denoted as SrNb2O 6-x -2 nanofibers.
[0075] Example 3
[0076] 10 mg of the SrNb2O6 nanofibers prepared in Comparative Example 1 were weighed and immersed in 10 mL of 0.15% ethanol aqueous solution for 1 h, and then transferred to a tube furnace. The vacuum degree in the tube was set to -0.1 MPa, and then the temperature was raised to 300 ° C at a rate of 2 ° C / min and kept for 1 h to obtain SrNb2O6 nanofibers with surface periodic acid-base pairs. 6-x Nanofiber material, denoted as SrNb2O 6-x -3 nanofibers.
[0077] Structural characterization
[0078] The SrNb2O prepared in Example 3 6-x -3 nanofibers were observed by scanning electron microscopy, and the results were as follows Figure 1 As shown. Figure 1 It can be observed that the multilayer SrNb2O 6-x -3 nanofibers form a hinge network. Among them, SrNb2O 6-x -3 The diameter of nanofibers ranges from 30 to 50 nm.
[0079] The SrNb2O prepared in Examples 1 to 3 6-x The nanofiber material and the SrNb2O6 nanofiber prepared in Comparative Example 1 were characterized by X-ray diffraction. Figure 2 As shown. Figure 2 It can be seen that SrNb2O 6-x It has a similar monoclinic phase to the original SrNb2O6 (JCPDS#28-1243), indicating that the effect of secondary annealing on the crystal structure of SrNb2O6 is negligible.
[0080] The SrNb2O prepared in Example 3 6-x -3 nanofibers were observed by electron microscopy with spherical aberration correction, and the results are as follows Figure 3 As shown. Figure 3 It can be seen that Nb and Sr on the surface are distributed periodically.
[0081] The SrNb2O prepared in Example 3 6-x -3 nanofibers and SrNb2O6 nanofibers prepared in comparative example 1 were subjected to electron paramagnetic resonance. The results are as follows Figure 4 As shown. Figure 4 It can be seen that the SrNb2O6 nanofibers formed after annealing 6-x The nanofibers contain oxygen defects, that is, the electrons in the vacancies tend to be attracted to the transition metal ion Nb 5+ Transfer, so that part of Nb 5+ Restore to Nb 4 + .
[0082] The SrNb2O prepared in Example 3 6-x -3 nanofibers and SrNb2O6 nanofibers prepared in comparative example 1 were subjected to UV-visible light absorption spectrum test, and the results are shown in Figure 5 .Depend on Figure 5 It can be seen that after removing the surface oxygen atoms to expose the periodic acid-base sites, SrNb2O 6-x -3 The optical absorption of nanofibers in the visible-infrared region (wavelength range 400nm to 1500nm) is significantly enhanced, which means that the material can significantly improve the utilization rate of photons.
[0083] The SrNb2O prepared in Example 3 6-x -3 nanofibers and SrNb2O6 nanofibers prepared in comparative example 1 were subjected to carbon dioxide isothermal adsorption experiments at an adsorption temperature of 25°C, and isothermal adsorption curves were drawn. The results are shown in Figure 6 As shown. Figure 6 It can be seen that SrNb2O 6-x -3 nanofibers have stronger carbon dioxide adsorption capacity than SrNb2O6 nanofibers.
[0084] Application Example 1
[0085] Add 10 mL of deionized water into the container and then add 1.5 mg of SrNb2O prepared in Example 1. 6-x -1 nanofibers were used as photocatalysts, coated on a glass sheet with an area of 2×2.5 cm, dried, and placed in a closed reactor made of quartz; a 300W xenon lamp was used as the light source, with a light density of 150mW / cm 2 In order to avoid the temperature of the reaction system rising due to long-term illumination, the reactor is placed above the fan to ensure constant temperature, and finally high-purity CO2 gas is introduced into the sealed reactor.
[0086] The change of product gas with illumination time was measured by gas chromatograph equipped with FID detector (hydrogen flame ionization detector). Figure 7 and Table 1.
[0087] Table 1 SrNb2O 6-x -1 Carbon monoxide yields at different times in nanofiber photocatalytic CO2 reduction reaction
[0088] Time / min 60 120 180 Carbon monoxide production / μmol / g 13.25 27.69 40.69
[0089] Depend on Figure 7 As shown in Table 1, the SrNb2O prepared by the present invention 6-x -1 nanofiber photocatalyst can photocatalytically reduce carbon dioxide to carbon monoxide, with the carbon monoxide generation rate being 13.56 μmol / g / h.
[0090] Application Example 2
[0091] The only difference from Application Example 1 is that SrNb2O 6-x -1 nanofibers were replaced with SrNb2O prepared in Example 2 6-x -2 nanofibers as photocatalysts.
[0092] The changes of product gas with illumination time were measured by gas chromatograph equipped with FID detector. Figure 7 and Table 2.
[0093] Table 2 SrNb2O 6-x -2 Carbon monoxide yields at different times in nanofiber photocatalytic CO2 reduction reaction
[0094] Time / min 60 120 180 Carbon monoxide production / μmol / g 29.59 61.1 92.36
[0095] Depend on Figure 7 As shown in Table 2, the SrNb2O prepared by the present invention 6-x -2 nanofiber photocatalyst can photocatalytically reduce carbon dioxide to carbon monoxide, with the carbon monoxide generation rate being 30.79.μmol / g / h.
[0096] Application Example 3
[0097] The only difference from Application Example 1 is that SrNb2O 6-x -1 nanofibers were replaced with SrNb2O prepared in Example 3 6-x -3 nanofibers as photocatalysts.
[0098] The changes of product gas with illumination time were measured by gas chromatograph equipped with FID detector. Figure 7 and Table 3.
[0099] Table 3 SrNb2O 6-x -3 Carbon monoxide yields at different times in nanofiber photocatalytic CO2 reduction reaction
[0100] Time / min 60 120 180 Carbon monoxide production / μmol / g 18.21 36.13 53.89
[0101] Depend on Figure 7 As shown in Table 3, the SrNb2O prepared by the present invention 6-x -3 nanofiber photocatalyst can photocatalytically reduce carbon dioxide to carbon monoxide, with the carbon monoxide generation rate being 17.96 μmol / g / h.
[0102] Comparative application example 1
[0103] The only difference from Application Example 1 is that SrNb2O 6-x-1 nanofibers were replaced by SrNb2O6 nanofibers prepared in Comparative Example 1 as photocatalysts.
[0104] The change of product gas with illumination time was measured by gas chromatograph equipped with TCD detector. Figure 7 and Table 4.
[0105] Table 4 Carbon monoxide production at different times in SrNb2O6 nanofiber photocatalytic CO2 reduction reaction
[0106] Time / min 60 120 180 Carbon monoxide production / μmol / g 10.21 20.39 30.36
[0107] Depend on Figure 7 As shown in Table 4, the SrNb2O6 nanofiber photocatalyst prepared in Comparative Example 1 can photocatalytically reduce carbon dioxide to carbon monoxide, but the rate of generating carbon monoxide is relatively slow, which is 10.12 μmol / g / h.
[0108] From the data in Tables 1 to 4, it can be seen that the SrNb2O prepared by the present invention 6-x Nanofiber photocatalysts have higher catalytic activity than SrNb2O6 nanofiber photocatalysts, and the rate of carbon monoxide precipitation is 1.34 to 3.04 times that of SrNb2O6 nanofiber photocatalysts.
[0109] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A SrNb2O 6-x The nanofiber material comprises SrNb2O6 nanofibers, and Lewis acid-base pairs and oxygen vacancies distributed on the surface of the SrNb2O6 nanofibers; in the Lewis acid-base pairs, the Lewis acid is Sr 2+ , the Lewis base is Nb 4+ The Lewis acid and Lewis base are arranged periodically respectively; the SrNb2O6 nanofibers are composed of SrNb2O6 crystals.
2. SrNb2O according to claim 1 6-x Nanofiber material, characterized in that The SrNb2O6 crystal is a monoclinic crystal.
3. SrNb2O according to claim 1 or 2 6-x The method for preparing the nanofiber material comprises the following steps: The SrNb2O6 nanofibers are immersed in a reducing organic solution and then taken out to obtain SrNb2O6 nanofibers with the reducing organic solution attached to the surface; the SrNb2O6 nanofibers are composed of SrNb2O6 crystals; The SrNb2O6 nanofibers with the reducing organic solution attached to their surfaces are annealed under vacuum conditions. 5+ Reduced to Nb 4+ At the same time, oxygen vacancies are formed to obtain the SrNb2O 6-x Nanofiber materials.
4. The preparation method according to claim 3, characterized in that: The reducing organic matter in the reducing organic matter solution includes alcohol and / or aldehyde; the concentration of the reducing organic matter solution is 0.05-0.5%.
5. The preparation method according to claim 3, characterized in that: The annealing temperature is 200-400° C., and the insulation time is 1-2 hours.
6. The preparation method according to claim 3, characterized in that: The preparation method of the SrNb2O6 nanofiber comprises the following steps: dissolving a divalent strontium salt, a pentavalent niobium salt and an organic template agent in a solvent to obtain a spinning solution; Electrospinning the spinning solution to obtain metal salt-template composite nanofibers; The metal salt-template composite nanofibers are calcined in an air atmosphere to obtain the SrNb2O6 nanofibers.
7. The preparation method according to claim 6, characterized in that: The calcination temperature is 500-850° C., and the heat preservation time is 1-6 hours.
8. The preparation method according to claim 6, characterized in that: The organic template includes one or more of polyvinyl pyrrolidone, polyacrylonitrile and polyvinyl alcohol.
9. The preparation method according to claim 6 or 8, characterized in that: The molar ratio of Sr in the divalent strontium salt to Nb in the pentavalent niobium salt is 1:2; the mass ratio of the total mass of the divalent strontium salt and the pentavalent niobium salt to the mass of the organic template is (0.2-0.6):
1.
10. SrNb2O according to claim 1 or 2 6-x Nanofiber material or SrNb2O prepared by the preparation method according to any one of claims 3 to 9 6-x Application of nanofiber materials as photocatalysts in photocatalytic reduction of CO2.
